Genealogi Pengklaiman Kanjeng Raden Tumenggung (KRT) Sumodiningrat sebagai Habib Hasan Bin Yahya - M. Yaser Arafat (Local History & Heritage, 2025)
Over the past two decades, a controversial historical claim has circulated asserting that Kanjeng Raden Tumenggung (KRT) Sumodiningrat, a prominent official of the Yogyakarta Sultanate who died during the Sepehi War of 1812, was in fact a habib named Hasan bin Yahya, whose tomb is alleged to be located in Lamper Kidul, Semarang, while the tomb in Jejeran is attributed to his brother, Ahmad bin Yahya. This study investigates the genealogy and construction of this claim by posing the central question of how, when, and through what actors and discursive mechanisms the claim emerged and gained legitimacy. Employing a genealogical approach grounded in historical and anthropological scholarship and complemented by a Foucauldian discourse analysis, the study examines both diachronic continuities and synchronic social processes. Methodologically, the research relies on a critical literature review and netnography to trace the diffusion of narratives across books, academic writings, and digital media platforms. The findings indicate that the claim first appeared around 2005 and expanded significantly through publications and online broadcasts, particularly YouTube, gaining authority through endorsement by a nationally influential Islamic scholar and his network. The study concludes that this narrative represents an organized, refined, and strategic form of historical claiming that intertwines scholarship, religious authority, and digital media.